Institute of Metals Division - The Kinetics of Creep During Hot Pressing of Loose Silver-Powder Aggregates - M. J. Salkind; F. V. Lenel; G. S. Ansell (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1965)
An experiment is described in which the growth of interparticle necks in an array of loose spherical silver powder at temperatures near 300°C was determined by measuring changes in the electrical resistance of the array. The activation energy for neck growth of contacts was derived by abruptly changing temperature and noting the change in the rate of neck growth. Since the experiments were run under an external load, the changes in activation energy with stress could he determined. The activation energy was found to decrease rapidly with increasing stress. It is concluded that the material transport in the experiments is one of plastic flow by dislocation motion. The variation of activation energy with stress is typical for cross slip of dislocations, an important material transport mechanism in the temperature range investigated. THE process in which powder compacts or aggregates of loose powder are held at an elevated temperature under an external load is called hot pressing or sintering under pressure by powder metallurgists. In this investigation the early stages of this process as applied to loose spherical silver- powder aggregates were studied. The powder particles were approximately 100µ in diameter and the temperature was near 300°C, i.e., below one half of the melting point of silver in degrees Kelvin, where volume diffusion is not expected to contribute to sintering. In the process, the contact or neck areas between powder particles grow. Since this involves plastic deformation of the particles under a constant external load (even though not under constant stress) it would be termed creep by mechanical metallurgists. On the other hand, the growth in neck area observed in compacts or loose-powder aggregates held at elevated temperature without the application of an external load is termed sintering by powder metallurgists. During sintering the major driving force is the stress due to surface tension. However, even when no load is placed on the compact or powder aggregate, an external stress, i.e., gravity, plays an important role in sintering in addition to those stresses arising from surface tension, as was shown in two previous investigations.'" It is therefore postulated that no sharp dividing line can be drawn between the phenomena of "creep" and "sintering". Different material transport mechanisms may be involved in either of these phenomena, but they will depend upon the temperature and the level of stress, but not necessarily upon the nature of the driving force: surface tension or external load. At the low temperatures of this investigation, an external stress much higher than the stress due to surface tension is necessary to obtain measurable rates of neck growth. In order to avoid misunderstanding this phenomenon will be called "creep". The rate of growth in contact area in the loose silver-powder aggregates was determined by meas-